PELAKSANAAN PEMBERIAN BANTUAN HUKUM SECARA PRODEO TERHADAP TINDAK PIDANA NARKOTIKA DI POS BANTUAN HUKUM PENGADILAN NEGERI BUKITTINGGI - Susilawati, Romi; Sukmareni, Sukmareni; Munandar, Syaiful (Yayasan Pendidikan Islam Almatani, 2023)
As we all know, every Indonesian who has a case in court, both criminal and civil, has the right to get legal aid services at the Legal Aid Post, which is then known as Posbakum, which is a post in every District Court in Indonesia which was formed by the Supreme Court. The Republic of Indonesia, namely Perma Number 1 of 2014, has the duty to provide legal aid services to underprivileged people who are blind to the law in court. This type of research is classified in the type of empirical juridical research. This type of research is descriptive analysis. The results of research and discussion there are three main things that can be concluded. First, the Bukittinggi district court legal aid post as a legal service provider on a free basis in narcotics crime cases at the Bukittinggi district court, some of the legal services are running and other legal services have no problems because. Second, in the implementation of the provision of legal services, there are obstacles or obstacles. Third, the efforts made in overcoming obstacles in the provision of prodeo legal services to the underprivileged at the Bukittinggi District Court are implementing efforts to minimize obstacles in providing legal aid services at the Bukittinggi District Court Posbakum.